The nexus of monetary policy and economic growth: Empirical study from Indonesia - Idah Zuhroh (Journal of Innovation in Business and Economics, 2021)
This study investigates the short and long-term relationships between monetary policy and economic growth in Indonesia. The vector error correction model (VECM) applies to tackle the research objective and use quarterly data from 2004 to 2019. The result shows a significant negative effect of inflation in the short term, and other variables are insignificant. Inflation and exchange rate have a significant positive impact in the long term, and money supply has a negative coefficient. Besides, interest rates do not significantly affect Indonesia's economic growth. Findings of the negative long-term impact of the money supply on growth are not a good indication; we argue that this anomaly needs to be taken seriously by the authorities to maintain economic stability and sustainable growth.